Coping Strategies Among Indonesian College Students During The Covid-19 Pandemic - Putri, Triyana Harlia; Priyono, Djoko; Fitrianingrum, Iit (Malaysian Journal of Medicine and Health Sciences, 2022)
Introduction: Several steps have been taken to reduce opportunities for spreading diseases COVID-19. Coping strategies are the main tool individuals use to minimize situations that are considered dangerous. College students cannot use coping strategies that are typically done outside, due to the limitations of lockdown in their respective areas. The aim of this study was to identify differences in coping strategies used by students during the pandemic in West Kalimantan, Indonesia. Method: A cross-sectional survey approach was conducted among Indonesian college students. The data for the study were collected from students acquiring education at public/private Universities/Academies/Institutes spread throughout West Kalimantan Province in Indonesia. The sample size was 663 students, and the sampling strategies used a snowball technique. The Brief-COPE inventory was used to measure coping strategies. Results: The majority of the 663 students used adaptive coping (41.94 ±8.641). The mean score was highest for emotional support (6.44 ± 1.430) and active coping (6.10 ± 1.467), followed by religion (6.00 ± 1.394), with the lowest score for substance use (4.24 ± 1.368). We did not found significant differences between the sociodemographic subgroups except gender on subscales for religion, active cope, emotional support, and substance. Conclusion: Adaptive coping is more widely used by students in maintaining mental health than maladaptive coping. There were high scores on the subscales measuring the use of emotional support, active coping, and religion. Although many students use positive coping, students who use maladaptive coping need intervention from the campus, such as by providing online counseling services.